Two-Stage Image Segmentation Scheme Based on Inexact Alternating Direction Method. Issue 3 (20th July 2016) - Zhi, Zhanjiang; Sun, Yi; Pang, Zhi-Feng
Abstract: Image segmentation is a fundamental problem in both image processing and computer vision with numerous applications. In this paper, we propose a two-stage image segmentation scheme based on inexact alternating direction method. Specifically, we first solve the convex variant of the Mumford-Shah model to get the smooth solution, the segmentation are then obtained by apply the K -means clustering method to the solution. Some numerical comparisons are arranged to show the effectiveness of our proposed schemes by segmenting many kinds of images such as artificial images, natural images, and brain MRI images.